154 Evaluation of repeated exposure to lipopolysaccharide on vaginal temperature and complete blood count in two-year-old Brahman heifers. (29th July 2019) - O'Daniel, Sydney E; Riley, David G; Neuendorff, Don A; Dailey, Jeffery W; Carroll, Jeffery A; Randel, Ronald D; Welsh, Thomas H
Abstract: The effects of escalating lipopolysaccharide (LPS) doses on vaginal temperature (VT) and complete blood count (CBC) were evaluated to develop a model of low-level inflammatory response in cattle. Brahman heifers (2-yr-old; 326 kg BW) paired by birthdate, sire, and weaning temperament score were fitted with self-contained, indwelling vaginal temperature probes 7 d before initiation of treatment (d 0) and randomly assigned to Control (n = 6) or LPS (n = 6) treatment. Heifers were maintained as a group with free choice access to Coastal bermudagrass hay and fed 3.6 kg of a 3:1 corn:corn gluten grain mix per head per day. Heifers were weighed, BCS recorded, and blood samples were collected weekly by jugular venapuncture before delivery of treatments. Treated heifers received LPS (from Escherichia coli) via subcutaneous injection in the neck (d 0: 0.25 μg / kg BW; d7: 0.50 μg /kg BW; d 14: 0.75 μg /kg BW) and Control heifers received saline. Sickness behavior score (SBS) was monitored at 30-min intervals for 12 hr after LPS. Treatment was the fixed effect of interest. Random effects included sire and day repeated with heifer as the subject. No dose-treatment interactions were detected. The SBS did not change after subcutaneous LPS or saline (P > 0.1). Neutrophil and lymphocyte numbers 7 d after each injection were not affected by LPS (P > 0.1). A febrile response began within 1 hr and persisted up to 14 hr after LPS injections. The febrile effect of the 0.25 μg LPS dose was less pronounced (P < 0.05) than that of the 0.50 μg and 0.75 μg LPS doses which were similar to one another. Lipopolysaccharide treatment increased maximum VT (P < 0.0001), hastened time to attain maximum VT (P = 0.0429), and increased the change in VT (P < 0.0001). Weekly subcutaneous injection of LPS facilitates the study of the effect of sub-clinical illness in beef cattle.